ЕNVIRONMENTAL POLICY IN THE PROGRAMS OF POLITICAL PARTIES IN MACEDONIA - Veljanoska, Svetlana (Journal of process management and new technologies, 2021)
This paper aims to analyze whether, how much and in what way environmental policies are developed in the programs of political parties in Macedonia. The paper will initially develop the terms party, party program and policies in the field of ecology.The central topic of the paper is the environmental policy in the programs of the parties and their systematization in terms of the topics on which they base their policies.The author will try to contribute to the typology of parties in terms of their attitude towards environmental issues.